Political terror: Social analysis study - Ramadan Mohamed, Hamdan (Al-Adab Journal, 2021)
The research aimed to identify the phenomenon of political terrorism and its causes, because the issue of terrorism is now occupying the world and its political and international systems due to its effects on the system of relations of society with its individuals and institutions, so that its forms and motives varied, in addition to that the importance of the research is evident from the importance of the topic we are dealing with, and we used the method Descriptive and historical analysis of the topic, and the research reached several conclusions, the most important of which are: Political terrorism is a socio-political phenomenon simultaneously. The phenomenon of political terrorism is taking place today more than ever before with attention to it with the aim of finding radical solutions to it The world lives today at the mercy of terrorism and the people of the world no longer have a choice in leaving this infernal machine.